Decision-making and gaze behavior of basketball players in 3-on-3 Pick'n Roll play - Sakselin, Mira-Maaret (2020)
Introduction. In complex play-situations such as basketball pick’n roll, players must use their vision to read the game, plan an action, and execute a motor response according to the goal. The eye-tracking research in sports offers an understanding of how gaze is related to performance and how athletes make decisions in complex and time-constrained situations. The critical visual information, advanced cue points, or search patterns could be identified, and this information could be used to develop coaching. The purpose of the current study is to assess the differences in gaze behavior between different decisions, defensive plays, and level of field of vision in 3-on-3 basketball pick’n roll.